Perlindungan Hak Cipta Lagu Yang Di Nyanyikan Ulang Tanpa Izin Pencipta Yang Di Unggah Di Media Sosial - Nani Novendo Sidabariba; Rory Jeff Akyuwen; Agustina Balik (PATTIMURA Law Study Review, 2023)
The problem in this thesis is about acts of copyright infringement in the form of cover songs on the YouTube platform. This research aims to make everyone understand that any action involving the use of other people's copyrights, either in part or in whole, is required to obtain prior permission from the creator and/or copyright holder. Based on article 9 of the Copyright Law No. 28 of 2014 it can be seen that everyone is prohibited from publishing creations, copying creations in all its forms, and is prohibited from exercising economic rights without the author's permission, and is prohibited from duplicating and/or using commercial creations. The method used in this research is normative juridical with statutory approach (statute approach) and conceptual approach (conceptual approach). The legal materials used are primary legal materials, secondary which are analyzed qualitatively. Based on this research, copyright protection for songs that are sung again consists of preventive and repressive legal protection. Preventive legal protection is carried out by supervising, coordinating and cooperating with the dissemination of re-sung song content, recording of creations, and closing related content and/or rights in electronic systems. Repressive protection in the form of compensation fines. The legal consequence received by the party who sings the song without the creator's permission is to pay compensation to the copyright holder in accordance with Article 1365 of the Civil Code. in the form of negotiation, mediation, conciliation, expert opinion and also arbitration.